Exploring gender differences in Norwegian eighth-grade students: the role of passion, grit, growth mindset, self-efficacy, compassion, courage, and wellbeing - Litlabø, Vegard Renolen; Haga, Monika; Richter, Isabell; Sigmundsson, Hermundur (Frontiers in Education, 2026)
The purpose of this study was to survey how middle school students perceive their passion, grit, growth mindset, self-efficacy, compassion, courage, school safety, school wellbeing and flourishing. Gender differences were explored in both baseline levels and correlations of these constructs. A cross-sectional survey was conducted on 7260 Norwegian 12–14 year old adolescents. T-tests and correlation analyses were used explore gender-specific patterns in 3539 boys and 3721 girls. Results showed gender differences in factors for psychological resilience, with boys reporting significantly higher levels of passion, grit, growth mindset, self-efficacy, self-compassion, courage, school wellbeing, and school safety. Girls scored significantly higher on compassion for others and reported receiving more compassion from others. No significant difference was found in levels of flourishing. Although boys scored higher on all motivational factors included in this study, girls showed stronger associations between self-efficacy, grit, and growth mindset which suggests a more cohesive motivation profile. In girls, school wellbeing showed stronger associations with perceived safety as well as both received and self-directed compassion compared to boys. For boys, compassion toward others showed a stronger correlation with both self-compassion and the compassion they received from others. These patterns suggest that girls may particularly benefit from increased self-efficacy and self-directed compassion, while boys may gain from developing more compassion toward others. Future research is needed to explore how these patterns evolve over time.